Entrepreneurship issues and challenges in Kerala and the role of University of Kerala in fostering an Entrepreneurial culture and the need for entrepreneurship education - K.S. Chandrasekar Jubi R
Even though India is a big country, it has many problems. One of them being the unemployment and gainful employment. It was found that unless entrepreneurial awareness is created, there will be social chaos. In this context, the government of Kerala, University of Kerala have started new initiatives like ED Cell, ED subcentres, Akshaya, Kudumbasree etc., This paper will throw light on the need for entrepreneurship as a curriculum in schools and colleges and the role played by University of Kerala in fostering entrepreneurial culture.